François Lamy’s Cartesian Refutation of Spinoza’s Ethics - Jack Stetter (Journal of Modern Philosophy)
François Lamy (1636–1711), a Benedictine monk and Cartesian philosopher whose extensive relations with Arnauld, Bossuet, Fénélon, and Malebranche put him into contact with the intellectual elite of late-seventeenth-century France, authored the very first detailed and explicit refutation of Spinoza’s Ethics in French, Le nouvel athéisme renversé (1696). Regrettably overlooked in the secondary literature on Spinoza, Lamy is an interesting figure in his own right, and his anti-Spinozist work sheds important light on Cartesian assumptions that inform the earliest phase of Spinoza’s critical reception in the seventeenth-century. I begin by presenting Lamy’s life and the contentious state of Spinoza’s French reception in the 1680 and 1690s. I then discuss a central argument in Lamy’s refutation, namely the Cartesian objection that Spinoza’s account of the conceptual independence of attributes is incompatible with the theory of substance monism. Contrasting Lamy’s objection with questions put to Spinoza by de Vries and Tschirnhaus, I maintain that by exhibiting the direction Spinoza’s views on substance and attribute took in maturing we may accurately assess the strength of Spinoza’s position vis-à-vis his Cartesian objector, and I argue that, in fact, Spinoza’s mature account of God as an expressive ens realissimum is not vulnerable to Lamy’s criticism. In conclusion, I turn to Lamy’s objection that Spinoza’s philosophy is question-begging in view of Spinoza’s account of God, and I exhibit what this point of criticism tells us about the intentions of the first French Cartesian rebuttal of the Ethics.